Significance of arterial hyperoxia and relationship with case fatality in traumatic brain injury: a multicentre cohort study. Issue 7 (21st June 2013) - Rincon, Fred; Kang, Joon; Vibbert, Matthew; Urtecho, Jacqueline; Athar, M Kamran; Jallo, Jack
Abstract : Objective: In this retrospective multi-centre cohort study, we tested the hypothesis that hyperoxia was not associated with higher in-hospital case fatality in ventilated traumatic brain injury (TBI) patients admitted to the intensive care unit (ICU). Methods: Admissions of ventilated TBI patients who had arterial blood gases within 24 h of admission to the ICU at 61 US hospitals between 2003 and 2008 were identified. Hyperoxia was defined as PaO2 ≥300 mm Hg (39.99 kPa), hypoxia as any PaO2 <60 mm Hg (7.99 kPa) or PaO2 /FiO2 ratio ≤300 and normoxia, not defined as hyperoxia or hypoxia. The primary outcome was in-hospital case fatality. Results: Over the 5-year period, we identified 1212 ventilated TBI patients, of whom 403 (33%) were normoxic, 553 (46%) were hypoxic and 256 (21%) were hyperoxic. The case-fatality was higher in the hypoxia group (224/553 [41%], crude OR 2.3, 95% CI 1.7-3.0, p<.0001) followed by hyperoxia (80/256 [32%], crude OR 1.5, 95% CI 1.1-2.5, p=.01) as compared to normoxia (87/403 [23%]). In a multivariate analysis adjusted for other potential confounders, the probability of being exposed to hyperoxia and hospital-specific characteristics, exposure to hyperoxia was independently associated with higher in-hospital case fatality adjusted OR 1.5, 95% CI 1.02-2.4, p=0.04. Conclusions: In ventilated TBI patients admitted to the ICU, arterial hyperoxia was independently associated with higher in-hospital case fatality. In the absence of results from clinical trials, unnecessary oxygen delivery should be avoided in critically ill ventilated TBI patients.